1999
DOI: 10.1103/physrevlett.82.1768
|View full text |Cite
|
Sign up to set email alerts
|

Massive and Massless Behavior in Dimerized Spin Ladders

Abstract: We investigate the conditions under which a gap vanishes in the spectrum of dimerized coupled spin-1/2 chains by means of Abelian bosonization and Lanczos diagonalization techniques. Although both interchain (J ′ ) and dimerization (δ) couplings favor a gapful phase, it is shown that a suitable choice of these interactions yields massless spin excitations. We also discuss the influence of different arrays of relative dimerization on the appearance of non-trivial magnetization plateaus.PACS numbers: 75.10. Jm, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
62
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 27 publications
(49 reference statements)
7
62
0
Order By: Relevance
“…At J ⊥ = 0 the model (58) is known as the spin-orbital chain [29] and has been recently studied by different groups (see e.g. [30,8,31]). If J ⊥ = 0 but |V | is large enough, the model (58) occurs in a non-Haldane, spontaneously dimerized phase where the spectrum is entirely incoherent and consists of pairs of topological kinks [13].…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At J ⊥ = 0 the model (58) is known as the spin-orbital chain [29] and has been recently studied by different groups (see e.g. [30,8,31]). If J ⊥ = 0 but |V | is large enough, the model (58) occurs in a non-Haldane, spontaneously dimerized phase where the spectrum is entirely incoherent and consists of pairs of topological kinks [13].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…[5]), are excellent candidates for such a scenario. A nice example of this kind has been recently given by Martin-Delgado et al [6,7] (see also [8]) who considered the standard J-J ⊥ two-leg spin ladder (J, J ⊥ > 0)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition some theoretical and/or numerical analyses predicted that a magnetization plateau appears in various other systems; the polymerized chains [13][14][15][16][17][18][19][20][21][22][23], the S = 3/2 chain [24][25][26][27], the frustrated spin ladder [28][29][30][31][32], several generalized spin ladders [33][34][35][36][37][38], distorted diamond type spin chain [39][40][41] and some layered sytems [42,43]. Using the Lieb-Schultz-Mattis theorem [44], a general necessary condition for the presence of the plateau was derived [24] as…”
Section: Introductionmentioning
confidence: 99%
“…A number of theoretical studies have also considered the effect of an explicit dimerization term on the Heisenberg spin-ladder without frustrating (diagonal) interactions [20][21][22][23][24][25][26] . Interestingly, these works found that although a dimerization term opens a gap when added to a gapless spin-chain, adding such a term to a gapped spin ladder can lead to a gapless phase for suitably tuned dimerization and exchange couplings.…”
Section: Introductionmentioning
confidence: 99%